2004
DOI: 10.4161/cbt.3.8.994
|View full text |Cite|
|
Sign up to set email alerts
|

The PIK3CA gene is mutated with high frequency in human breast cancers

Abstract: The phosphatidylinositol 3-kinases (PI3Ks) are known regulators of cellular growth and proliferation. It has recently been reported that somatic mutations within the PI3K subunit p110alpha (PIK3CA) are present in human colorectal and other cancers. Here we show that thirteen of fifty-three breast cancers (25%) contain somatic mutations in PIK3CA, with the majority of mutations located in the kinase domain. These results demonstrate that PIK3CA is the most mutated oncogene in breast cancer and support a role fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
424
8
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 603 publications
(461 citation statements)
references
References 12 publications
24
424
8
5
Order By: Relevance
“…Campbell et al (2004) reported 40% of mutation frequency in all 20 coding exons (new as well as previously reported mutations). Bachman et al (2004) and Campbell et al (2004) studies noted no association of the presence of PIK3CA mutations with other clinical factors. Saal et al (2005) reported 25% of PIK3CA mutation rate, in this study author found significant correlation between PIK3CA mutation and ER/PR positive and lymph node metastasis and Her2.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Campbell et al (2004) reported 40% of mutation frequency in all 20 coding exons (new as well as previously reported mutations). Bachman et al (2004) and Campbell et al (2004) studies noted no association of the presence of PIK3CA mutations with other clinical factors. Saal et al (2005) reported 25% of PIK3CA mutation rate, in this study author found significant correlation between PIK3CA mutation and ER/PR positive and lymph node metastasis and Her2.…”
Section: Discussionmentioning
confidence: 92%
“…These mutations were predominantly found in kinase and helical domain of PIK3CA. Frequently occurring mutation were found in exon-9 and exon-20 Bachman et al (2004). Reported that average 25% of breast cancers harbors mutation in either kinase or helical domain.…”
Section: Discussionmentioning
confidence: 99%
“…The YB-1/PIK3CA/uPA network promotes invasion A Astanehe et al genetic aberration found in breast cancer (Bachman et al, 2004;Samuels and Velculescu, 2004;Isakoff et al, 2005;Saal et al, 2005). Moreover, expression of the mutant PIK3CA increases PI3K activity and has been shown to be transforming (Bader et al, 2006;Horn et al, 2008;Zhang et al, 2008).…”
Section: Mda-mb-231mentioning
confidence: 99%
“…[4][5][6][7][8] PTEN is a lipid phosphatase that opposes the ability of phosphatidylinositol 3-kinase (PI3K) to phosphorylate Akt, 9,10 thereby functioning as a tumor suppressor. Although constitutive activation of Akt and/or PI3K is described in a growing list of solid tumors as a mechanism for transformation, [11][12][13][14][15] the most frequently mutated component of this pathway, by far, is PTEN, found to have an average mutation rate of 16% across many tumor types, to as high as 83% in endometrial cancers. 16 We have previously demonstrated that the PTEN protein is lost/reduced in 38% of human invasive breast cancers.…”
mentioning
confidence: 99%